Non-aqueous reverse micelles created with a cationic surfactant: Encapsulating ethylene glycol in BHDC/non-polar solvent blends - Agazzi, Federico Martin (2016)
We present results on a new system that forms non-aqueous reverse micelles (RMs) created with a cationic surfactant, benzyl-n-hexadecyldimethylammonium chloride (BHDC), encapsulating ethylene glycol (EG), in different nonpolar solvents blends of n-heptane:benzene. It is shown that a cationic surfactant forms RMs using EG as polar solvent without the addition of a co-surfactant. In particular, we analyzed the EG solubilization capacity, the droplet size values and the interface composition of EG/BHDC/n-heptane:benzene RMs, using dynamic light scattering (DLS) and the solvatochromic behavior of 1-methyl-8-oxyquinolinium betaine (QB) as molecular dye. The EG solubilization capacity depends on the external phase composition decreasing when the n-heptane content increases. Using DLS technique, we demonstrate the formation of RMs, and observe that for the same [EG]/[BHDC] ratio, the micellar size increases when n-heptane content increases. Using QB it was found that EG penetrates into the micellar interface changing dramatically the composition and the droplet-droplet interaction, in comparison when water is encapsulated.